Yb3+/Er3+ codoped Bi2O3-WO3-TeO2 pedestal type waveguide for photonic applications - Del Cacho, V. D.; Silva, D. M. da; Kassab, L. R.P. [UNESP]; Chávez, M. I.; Carvalho, D. O. (My University, 2012)
This work presents, for the first time to our knowledge, experimental results on pedestal waveguides produced with Yb3+/Er3+ codoped Bi2O3-WO3-TeO2 thin films deposited by RF Sputtering. It was obtained optical gain of 3.2dB, for 2.0 cm waveguide length, at 100 mW pump power, indicating that Yb3+/Er3+ codoped Bi2O3-WO3-TeO2 pedestal-type waveguides are good candidates for the production of active waveguide devices for photonic applications.